ANALISA SPASIAL PEMETAAN LOKASI WISATA AGRO (STUDI KASUS DI LOMBOK BARAT) - Ahmat Adil (Universitas Bumigora, 2016)
Lombok Barat is one of the districts on the island of Lombok and became a tourist destination, has the appeal of natural and cultural tourism. Conditions natural attractions consist of natural landscapes, protected forests and community forests, beaches, plantations, and the diversity of marine potential. One element of the plantation sector which is currently untapped optimally is an agro-tourism. Agro-tourism potential is addressed from the natural beauty of the plantation and production in the plantation sector is sufficiently developed. Geographical Information Systems produces data aspects of spatial and non-spatial data. The main characteristics of the geographic information system is the ability to analyze a system such as statistical analysis and overlay called spatial analysis by adding the dimension '(space)' or geography. Spatial analysis conducted with mengoverlay two maps which then generates a new map analysis results. Spatial analysis process includes activities to create a buffer around a point (point), line (line) and area (polygon), analyzing a map with points, lines and areas with the overlay method, intersection, union, identity, and clips. Based on the spatial analysis has been done it obtained the three locations that can be used for agro tourism, namely: a coffee plantation with an area of 9751995 m2, oil plantation area of 8.99343 million and 27.03261 million, vanilla and coffee plantations covering an area of 7,042,943 m2.